Metallurgy development of Ti-stabilized stainless steel - Qi-ming WANG; Guo-guang CHENG (工程科学学报, 2021)
Titanium is widely used in the manufacture of stainless steel due to its stabilizing ability of carbon and nitrogen, the pinning effect on grain growth, and strengthening effect, which are contributed by the formation of Ti(C, N) with different compositions, sizes, and distributions. Due to the excellent corrosion resistance, formability, and mechanical properties, Ti-bearing stainless steel is widely applied to daily life and priority industries, including petroleum, aerospace, nuclear power, and transportation. However, complex inclusions can be formed after Ti addition in the metallurgy process. Moreover, those inclusions have adverse effects on the metallurgy and the quality of stainless steel, including the clogging of the submerged entry nozzle, layered defects, and surface defects. Therefore, it is important to develop the metallurgy of Ti-stabilized stainless steel. This paper discussed and concluded the investigation development of Ti-bearing stainless steel regarding the fundamentals of metallurgy, the formation and control of oxides and TiN, heterogeneous nucleation, and the influence of Ti on the mechanical properties of stainless steel. First, oxides with high melting points, including Al2O3, spinel, and (MgO−Al2O3)rich−CaO−TiOx, generally cause the clogging of the submerged entry nozzle in the Ti-bearing stainless steel. The optimized addition of Al, Ca, and Ti, as well as the control of slag, can decrease the amount of oxides with a high melting point. Second, the formation and growth of TiN and complex TiN inclusions happen during the cooling and the solidification of the titanium-stabilized stainless steel, which can collide and aggregate to form TiN clusters. Moreover, macro-oxides can promote the formation of TiN clusters. However, TiN or complex TiN inclusions can also work as heterogeneous nuclei for δ-Fe during the solidification of stainless steel and promote the generation of an equiaxed fine-grain structure. In addition to forming compounds, titanium can present as a solid solution state in steel and promote the formation of ferrite in austenitic stainless steel or increase the ferrite fraction in duplex stainless steel with its strong ferrite forming ability, which is beneficial to the improvement of the mechanical properties of stainless steel casting.